UJI AKTIVITAS ANTIOKSIDAN LOTION EKSTRAK ETANOL BUNGA PISANG KEPOK (Musa acuminata x M. balbisiana) MENGGUNAKAN METODE DPPH (1,1-diphenyl-2-picryilhidrazil) - Husnani, Husnani; Natasya Putri Handayani; Nikita Puspa (Akademi Farmasi Yarsi Pontianak, 2024)
Kepok banana flower (Musa acuminate x M. balbisiana) is known to contain flavonoid, polyvenol and saponin compounds that function as antioxidants. The purpose of this study was to determine the antioxidant activity and to determine the IC50 value of lotion of kepok banana flower (Musa acuminate x M. balbisiana) as an antioxidant. Antioxidant activity testing of lotion of kepok banana flower (Musa acuminate x M. balbisiana). Ethanol extract of pisang bunga kapok was obtained by extraction using maceration method with 96% ethanol for 3x24 hours. Then the extract was formulated into lotion preparations with variations of banana flower extract, namely 0.4%, 0.6%, and 0.8%. The results of the preparation of pisang kepok flower (Musa acuminate x M. balbisiana) with various concentrations of extracts meet the requirements of a good lotion preparation. Furthermore, it was tested using the DPPH (1,1-diphenyl-2-picryilhydrazyl) method with vitamin C comparator measured at a wavelength of 516.20 nm. The results of the lotion test of ethanol extract of kepok banana flower have antioxidant activity with IC50 values at FI 0.4% (33.83µg/ml), FII 0.6% (27.85µg/ml), FIII 0.8% (10.04µg/ml). Based on the IC50 data, it can be seen that FIII with a concentration of 0.8% has a very strong antioxidant value compared to FI and FII lotions. Translated with DeepL.com (free version)